1995
DOI: 10.1002/macp.1995.021960616
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymerization of glycidol. Polymer structure and polymerization mechanism

Abstract: Glycidol (2-epoxy-1 -propanoi) was polymerized under the action of Lewis acids (BF,OEt,, SnCI,) and protonic acids (CF,COOH, CF,SO,H). Polymers with number-average molecular weights (a,) varying from 2500 to 6000 g/mol were obtained. The structure of obtained polymers was characterized by I3C and "Si NMR spectroscopy, and the amount of 1-3 units, 1-4 units and chain branches was determined. The structure of the polymers was related to the polymerization mechanism, especially to the contribution of activated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 7 publications
0
122
2
Order By: Relevance
“…Vandenberg [26] and later extended by Penczek [27] and Dworak [28]. Calculation of the degrees of branching, however, was only possible after Frey utilized inverse …”
Section: Inverse Gated 13 C Nmr Analysismentioning
confidence: 99%
“…Vandenberg [26] and later extended by Penczek [27] and Dworak [28]. Calculation of the degrees of branching, however, was only possible after Frey utilized inverse …”
Section: Inverse Gated 13 C Nmr Analysismentioning
confidence: 99%
“…The chemistry and polymerization of oxetanes have been reviewed by Penczek et al 10) . Ring-opening polymerization of glycidol under different conditions have been reported by different authors 11,12) . In the thermally induced cationic polymerizations, a sulfonium salt, i. e. benzyltetramethylenesulfonium hexafluoroantimonate, BTSSbF 6 , Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Structural and mechanistic details of such polymerization process have been reported and it was found that the structure of the polymers was related to the contribution of activated monomer mechanism in chain growth. [91] Deffieux and coworkers [92] proposed a new initiation system developed for monomer activated anionic polymerization of propylene oxide (PO), i.e., onium salts/ triisobutylaluminum, were applied to the polymerization of glycidyl methyl ether. At low to moderate temperature they yielded fast polymerization and allowed a controlled synthesis of linear poly(glycidyl methyl ether) with high molar masses (up to 100000 g mol…”
mentioning
confidence: 99%